2021
DOI: 10.51910/ijhdr.v19i4.1025
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle characterization of HOMOEO AGROCARE (Agro Homeopathic Drug) by HRTEM and EDS analysis

Abstract: Background: Use of Homeopathy as a therapeutic tool is still very nascent in plant science and agriculture. Therapies used for plant growth and diseases are not relevant for plants alone, but they also drastically influence the ecosystem of the organic world too. Use of pesticides and chemical fertilizers was a boon during the initial phase of green revolution around the world. Unfortunately, later they became the major reason of chronic illnesses like cancers and a cause for soil degradation all over. Current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…66 Using probing tools of nanoscience, many independent research groups confirmed that nanoparticles are present in ultra-high dilutions used as medicines in homeopathy. [23][24][25][26][27]67,68 The vigorous shaking process used in homeopathy increases the water pressure in the glass bottle substantially. A lot of bubbles and nanobubbles are formed.…”
Section: How Ultra-high Dilutions May Work As Nanomedicinesmentioning
confidence: 99%
“…66 Using probing tools of nanoscience, many independent research groups confirmed that nanoparticles are present in ultra-high dilutions used as medicines in homeopathy. [23][24][25][26][27]67,68 The vigorous shaking process used in homeopathy increases the water pressure in the glass bottle substantially. A lot of bubbles and nanobubbles are formed.…”
Section: How Ultra-high Dilutions May Work As Nanomedicinesmentioning
confidence: 99%
“…In the previously published electron microscopy studies [27,28], the results showed the presence of substances in UHDs, but these results did not include evidence of the exclusive characteristics of any type of UHDs and did have not the ability to distinguish them from each other. Under these circumstances, samples from eleven kinds of UHD were collected and the individual formed pattern (EOMs) are imaged.…”
Section: Structural Study Of Eomsmentioning
confidence: 85%
“…Various non-biological empirical studies show that UHDs have different physicochemical properties from their aqueous solution [17][18][19][20][21][22][23][24]. These differences were investigated and published in the field of pH [22], density [24], electrical conductivity [22,25,26], ultraviolet spectroscopy [19], Scanning Electron Microscopy [27,28], and calorimetric properties [25]. Some believe that the variations in these properties are in terms of a change in the structure of the solvent during the preparation techniques.…”
Section: Non-biological (Chemical/physical) Studies On High Dilutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, use of homoeopathic medicines can improve agricultural production by improving plant health and prevent and cure diseases, without the extensive use of pesticides that damage the organic life and environment. [9] In this issue, we have an original article by Jain et al, which demonstrates the benefits of application of potentized homoeopathic medicines in enhancing plant productivity through a placebo-controlled study. [10] We hope the learning from the article will encourage wide-ranging application of homoeopathy in agriculture.…”
mentioning
confidence: 99%